2016
DOI: 10.1002/pmic.201600221
|View full text |Cite
|
Sign up to set email alerts
|

Identification of low abundance cyclophilins in human plasma

Abstract: Cylophilins (Cyps) belong to the ubiquitously distributed enzyme class of peptidyl prolyl cis/trans isomerases (EC5.2.1.8), which are foldases capable of accelerating slow steps in the refolding of denatured proteins. At least 20 different Cyp isoenzymes are broadly distributed among all organs and cellular compartments in humans. Extracellularly localized Cyps came into the scientific focus recently because of their involvement in the control of inflammatory diseases, as well as viral and bacterial infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Elevated levels of CypB expression have been identified in HCC [ 10 ], breast cancer [ 11 ], pancreatic cancer [ 12 ], gastric cancer [ 13 ], and glioblastoma [ 14 ]. Both CypA and CypB are proposed as potential therapeutic targets and biomarkers for the diagnosis of inflammatory conditions [ 15 ]. Another member of the Cyp family, hCypH, also recognized as Ppih , assists in protein folding by catalyzing the cis-trans isomerization of proline imidic peptide bonds in oligopeptides [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of CypB expression have been identified in HCC [ 10 ], breast cancer [ 11 ], pancreatic cancer [ 12 ], gastric cancer [ 13 ], and glioblastoma [ 14 ]. Both CypA and CypB are proposed as potential therapeutic targets and biomarkers for the diagnosis of inflammatory conditions [ 15 ]. Another member of the Cyp family, hCypH, also recognized as Ppih , assists in protein folding by catalyzing the cis-trans isomerization of proline imidic peptide bonds in oligopeptides [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the transportation of Cyp40 has not been studied yet 33 , we conducted research on how it transfers between cells. Examination of the co-culture medium indicated that Cyp40 was not present in the exosomes (Fig.…”
Section: Three-pointmentioning
confidence: 99%
“…However, this problem can be tackled at the level of elution. An interesting strategy based on selective elution was recently examined .…”
Section: Monoliths For High‐throughput Protein Purification or Screeningmentioning
confidence: 99%